PENGARUH METODE INKUIRI TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VIII SMPN 3 WATAMPONE: THE EFFECT OF INQUIRY METHOD ON THE WRITING SKILL OF OBSERVATION REPORT TEXT OF CLASS VIII SMPN 3 WATAMPONE STUDENTS - Nurhalizah, Resky; Usman; Haliq, Abdul (Journal of Applied Linguistics and Literature, 2025)
The Influence of the Inquiry Method on the Writing Skills of Class VIII Students at SMPN 3 Watampone: 1) Describe the learning outcomes of writing observation report text before using the inquiry method for class VIII students at SMPN 3 Watampone, (2) Describe the learning outcomes for writing observation report text after using the inquiry method for class VIII students at SMPN 3 Watampone, (3) To find out the effect of using the inquiry method on the learning outcomes of writing text reports on observations of class VIII students at SMPN 3 Watampone. This research is kind of quantitative research. The research design was in One Group Pretest-Posttest Design. The results of data analysis show that: (1) the learning outcomes of writing observation report texts before using the inquiry method for Class VIII students at SMPN 3 Watampone are categorized as poor with an average score of 40.97; (2) the results of learning to write observation report texts after using the inquiry method for Class VIII students at SMPN 3 Watampone were categorized as close to adequate with an average score of 69.35; (3) the results of the hypothesis test show that the sig. (2-tailed) value is 0.000 < 0.05, so that the alternative hypothesis (Ha) is accepted, namely that there is an influence of the use of the inquiry method on the learning outcomes of writing text reports on observations of Class VIII students at SMPN 3 Watampone.